Otolaryngology--head and neck surgery rapid clinical and board review - Carlson, Matthew L. (Assistant professor of otolaryngology); Abel, Kathryn M. Van (Kathryn Mckinna Van); Archibald, David J.; Price, Daniel L. (Thieme, 2015)
This well-organized text for rapid clinical and board review contains high-yield facts using a question and answer format that covers all subspecialty topics in otolaryngology. It combines clinically relevant facts with hard-to-remember, commonly tested details and presents them in an easy-to-follow layout that allows clinicians to quickly review large amounts of information.